Risk Factors for Isolated Left Main Coronary Artery Disease (Ibrahim Cardiac Medical Journal, 2011)
Background & objective: Left main coronary artery (LMCA) stenosis (defined as 50 or > 50 percent narrowing of luminal diameter) usually has a bad prognosis unless revascularization done. Isolated left main coronary artery (ILMCA) disease is a rare clinical entity. Although it carries a grave prognosis, its etiology is not well-understood. Determining risk factors for ILMCA disease might be promising in the preventive strategy of ischemic heart diseases. The aim of this study was to determine the demographic and traditional risk factors for left main coronary artery disease. Methods: This cross-sectional study was done on patients who underwent coronary angiogram (CAG) at Ibrahim Cardiac Hospital & Research Institute from February 2005 to June 2009. Total number of procedures done in Cath Lab was 7103. Of them 6708(94%) cases underwent CAG. Only 18 of them (0.27%) had isolated left main lesion and were included as cases. Patients who did not have ILMCA were taken as controls. The number of controls selected was 8 times the number of cases (n = 144). Of them 3 were excluded because of incomplete data leaving 141 controls finally. Fifty or > 50% stenosis in the left main was considered as significant stenosis. Major demographic and clinical information of patients were collected from the database of the Institute and were compared between the case and control groups. Results: Of the 18 subjects who had ILMCA disease 44.4% exhibited stable angina, 27.8% had ACS. One third of these patients had normal ECG, ST-T changes in another one third of the patients and 11% had previous MI. 16.7% patients had wall motion abnormality in echocardiogram. Only 4 out of these 18 patients had ETT done before CAG and all were found positive. Patients with ILMCA disease were comparatively old (> 50 years) than the patients without ILMCA disease (p = 0.448). Females were more prevalent in the case group (27.8%) than that in the control group (22.2%) (p = 0.854). There was no significant difference between patients with or without ILMCA disease in terms of traditional risk factors for ischemic heart diseases like hypertension, diabetes, smoking habit, dyslipidemia and family history of ischemic heart diseases (p > 0.05). Conclusion: Isolated and significant LMCA disease is an unusual angiographic finding and presents most commonly as stable angina. A female preponderance is usually observed. The prevalence of atherosclerotic risk factors of these patients is similar to that of the general population undergoing coronary angiogram. Key words: Isolated left main disease; risk factors; coronary angiogram; significant lesion. Ibrahim Card Med J 2011; 1(1):17-21